Factors that impact the efficiency of cream separator machine for the food industry - Asogan, Arjun; Norazlianie, Sazali; Ramli, Junid; Wan Norharyati, Wan Salleh; Afdhal, Junaidi; Nurul Widiastuti, .; Fansuri, Hamzah; Gunawan, Triyanda; Hartanto, Djoko (Akademi Baru, 2024)
This study examines the variables that impact the effectiveness of cream separator machines in the dairy sector, with a specific emphasis on centrifugal force, temperature, and vibration. The process of cream separation, which is crucial in dairy production, has progressed from manual techniques to sophisticated mechanical centrifugal separators. The objective of this study is to optimize the performance of these machines, which is imperative due to the increasing need for low-fat skimmed milk. The study utilizes a disc centrifuge to examine the impact of centrifugal forces. Thesetup consists of more than 24 discs, which are used to measure the volume of fluid passing through the spaces between the discs and to determine the efficiency of separation. The experiments involved using flow rates of 600 ml/min, 1200 ml/min, and 1800 ml/min to alter the temperature from 7°C to 15°C, 25°C, and 35°C. The findings indicated that decreased temperatures significantly enhance the efficiency of skimming. The study also examines the impact of machine-induced vibration on the efficiency of separation. The study concludes that excessive vibration negatively impacts productivity, therefore, it is essential to incorporate vibration control into the design of separators. The key findings suggest that optimizing centrifugal force is crucial. Inadequate force leads to incomplete separation of fat, while higher flow rates decrease separation efficiency. Temperature regulation is equally crucial, and reducing temperatures enhances efficiency. Effective vibration control is essential for maintaining optimal separation quality. This study makes a valuable contribution to the advancement of cream separator machines by highlighting the importance of accurate management of centrifugal force, temperature, and vibration. This is crucial for enhancing productivity and meeting the requirements of the market. The findings offer valuable insights for the dairy industry, assisting in the development and functioning of advanced cream separators that provide enhanced performance and economic advantages for producers.